Nursery Method for Damping - off Disease in True Seed Cultivation of Cluster Onion - Fernando, M.S.W.; Silva, S.H.S.A. De (International Journal of Environment, Agriculture and Biotechnology, 2019)
Onion (Allium cepa L.) is an important cash crop grown in Sri Lanka. Cluster onion cultivation in Sri Lanka is mainly grown using mother bulbs as planting material. With the introduction of true seed technology, the costs of planting material can be reduced. In general, when using seeds, the plants must be raised in a nursery for 28 days before they can be planted in a field. However, there is a gap in nursery techniques when using seeds and while expanding onion cultivations using true seed. This is a negative factor in the expansion of seed technology for agro-industrial areas such as Jaffna, Kalpitiya, Sri Lanka, since they do continues cultivation in their farm land. Therefore, it is required to maintain an indoor nursery if the onion is expected raise from seeds. Two soil-borne diseases that cause true seed culture in Cluster onions are damping-off (caused by Fusarium spp., Pythium spp., and Rhizoctonia solani) and Fusarium basal rot. These are the main constraint to popularizing the true seed crop. Main objective of this study was to identify the best management method for nurseries to achieve a low incidence of damping – off disease, which will help to obtain a high number of healthy stands. The sterilized normal nursery soil mix used in nursery trays in the shade showed a significantly (p<0.05) lowest post-emergence damping – off disease incidences. To avoid the development of an undesirable microclimate, it is essential to use nursery trays with separate holes.